Concentrations of tire wear microplastics and other traffic-derived non-exhaust particles in the road environment. (December 2022) - Järlskog, Ida; Jaramillo-Vogel, David; Rausch, Juanita; Gustafsson, Mats; Strömvall, Ann-Margret; Andersson-Sköld, Yvonne
Graphical abstract: Highlights: Traffic-derived particles were quantified in various on– and near-road compartments. Runoff (sediment and water) contained the highest proportion of tire wear particles (up to 38 %) The use of studded tires seems to increase the concentration of bitumen. The fine fraction contained more tire and bitumen (mass and number) than the coarse fraction. The stormwater system is evidenced to be one of the major transport routes of tire wear particles. Abstract: Tire wear particles (TWP) are assumed to be one of the major sources of microplastic pollution to the environment. However, many of the previously published studies are based on theoretical estimations rather than field measurements. To increase the knowledge regarding actual environmental concentrations, samples were collected and analyzed from different matrices in a rural highway environment to characterize and quantify TWP and other traffic-derived non-exhaust particles. The sampled matrices included road dust (from kerb and in-between wheeltracks), runoff (water and sediment), and air. In addition, airborne deposition was determined in a transect with increasing distance from the road. Two sieved size fractions (2–20 µm and 20–125 µm) were analyzed by automated Scanning Electron Microscopy/Energy Dispersive X-ray spectroscopy (SEM/EDX) single particle analysis and classified with a machine learning algorithm into the following subclasses: TWP, bitumen wear particles (BiWP), road markings, reflecting glass beads, metals, minerals, and biogenic/organic particles. The relative particle number concentrations (%) showed that the runoff contained the highest proportion of TWP (up to 38 %). The share of TWP in kerb samples tended to be higher than BiWP. However, a seasonal increase of BiWP was observed in coarse (20–125 µm) kerb samples during winter, most likely reflecting studded tire use. The concentration of the particle subclasses within airborne PM80-1 decreases with increasing distance from the road, evidencing road traffic as the main emission source. The results confirm that road dust and the surrounding environment contain traffic-derived microplastics in both size fractions. The finer fraction (2–20 µm) dominated (by mass, volume, and number) in all sample matrices. These particles have a high potential to be transported in water and air far away from the source and can contribute to the inhalable particle fraction (PM10 ) in air. This highlights the importance of including also finer particle fractions in future investigations.